Risk and protective factors related to having a child with congenital heart diseases (CHD): a case-control study in Iran - Amini-Rarani, Mostafa; Karimi, Salah Eddin; SoleimanvandiAzar, Neda; Nosratabadi, Mehdi (Frontiers in Pediatrics, 2023)
Background: The heart is the first fully developed organ in early pregnancy, especially in the first trimester of pregnancy, so any factor that contributes to heart failure is life-threatening. Thus, it is important to identify the risk and preventive factors related to this disease and to provide a scientific basis for the control, prevention, management and treatment of Child with Congenital Heart Diseases (CHD). Objectives: As the etiology of CHD is multifactorial, to identify the risk and preventive factors, this study aimed to investigate the factors related to CHD in Tehran, Iran. Methods: The present case-control study was performed on 600 people including 200 mothers of children with CHD. Simple random sampling was performed in 2020. The control group was matched with the case group, and the data were analyzed by SPSS software at a significance level of 0.5. Results: The results showed that low socioeconomic status, low education, history of abortion, smoking, alcohol consumption, risk factor, consumption of folic acid, and prenatal care are the protective factors against CHD. Conclusion: According to the findings, our emphasis should be on preventive strategies, education of mothers and public health experts on the need for folic acid and pregnancy care, and cessation or reduction of alcohol and tobacco use, especially in families with low socioeconomic status and low levels of education.